Clinico-Pathological Parameter in Thyroid Carcinoma Subtypes - Elhashani, Abdelmalek; Nazih Shahbaz, Jeilan; Abdulrhman Shaqami, Sara; Burgeia, Arwa; M Garalla, Hanan (Faculty of Pharmacy, 2021)
Background: Thyroid carcinomas have a diversity of histologic subtypes and variants. However, the relation between tumor architecture and prognosis are still lacking in spite of thorough investigation. The aim of this study was to evaluate the prognostic value of subclassification, focusing on subtypes and variants, and to determine its relation to different clinicopathological features in patients with thyroid cancer. Method: This retrospective study of a total number of 184 patients with thyroid cancer cases diagnosed in the time period from 2003 until 2020 in the archive of the pathology department of the faculty of medicine, University of Benghazi with the medical reports from the oncology department in Benghazi Medical Center. Subsequently, correlations between age, sex, grading and the tumour stag were investigated. Results: A total of 184 samples were analysed. Among all studied cases, females formed 76.1% with a female to male ratio of 7: 2. The age of the studied cases ranged between 14-95 years old. The mean age of patients with thyroid malignancy was 40.5 years old. The percentage of patients ?40 years was 51%, while patients <40 years formed 49%. Microscopic examination of thyroid carcinomas revealed different types, including thyroid carcinoma and papillary carcinoma. Papillary carcinoma was found to be the most common type of thyroid malignancies among the studied patients affecting 89 (48.4%) patients. Among the 89 patients, 76 were females (85.4%) and 13 were males (14.6 %). The other carcinoma cases were follicular variant of papillary carcinoma (29.3%) 47 female and 7 male, Anaplastic carcinoma (17.4%) 24 females and 8 males. Follicular carcinoma (4.9%) most of them are female. In this study, patients with stage II malignancy were the most common 83 (45%), followed by grade III malignancy were 69 patients (38%). The least common was grade I malignancy which accounted only for 32 patients (17%). Conclusion: The current study showed that the thyroid carcinoma affected the median age group with the median being 39.7 years with female predominance gender. Papillary thyroid carcinoma was the most common than the other subtypes (48.37%). About (45%) of patients with histological grading II, and 38% of cases presented with stage IV. There appears to be an increased trend of thyroid carcinoma diagnosis which is being reported at an advanced stage in our region, justifying the usefulness of the histological staging and grading of thyroid carcinomas.